The protective role of tissue-resident interleukin 17A–producing gamma delta T cells in Mycobacterium leprae infection - Liu, Yan; Shi, Chao; Ma, Shanshan; Ma, Yuelong; Lu, Xinyuan; Zhu, Jianyu; Yang, Degang (Frontiers in Immunology, 2022)
Mycobacterium leprae is a kind of disease-causing bacteria, and results in leprosy in human. Gamma delta () T cell is a T cell subset which is presented in both human dermis and epidermis. These cells bridge innate and adaptive immune responses, and play critical roles in regulating anti-microbial defense, wound healing, and skin inflammation. Here, we investigated skin resident  T cells in patients with leprosy. Our data showed that  T cells significantly accumulated in skin lesions of leprosy patients with tuberculoid (TT) form. And, IL-23 could predominantly stimulate dermal  T cells to produce interleukin 17 (IL-17), a cytokine which may lead to disease protection. These  T cells expressed a specific set of surface molecules, and majority of these cells were V1+. Also, IL-23 could stimulate the expansion of dermal  T cells expansion. Moreover, our results revealed that the transcription factor RORt was responsible for IL-17A expression in leprosy lesion. Therefore, these data indicated that IL-23-responsive dermal  T cells were the major resource of IL-17A production in the skin, and could be a potential target in the treatment of leprosy.